Consequences from workplace aggression or violence - Ali Mohamed, Ashgar Ali (LexisNexis Malaysia Sdn. Bhd., 2017)
Workers' safety and health at the workplace is a duty imposed on the employer. The employer must ensure not only a safe system of work but also a safe place of work. Safe place of work relates to the employer's responsibility to ensure that the work site is reasonably safe and to take reasonable precautions to protect workers against danger The employer is not required to insure them and to protect them against all risks of any kind but he is obliged to provide a reasonably safe place of work and to take reasonable care for his employees. The workplace should be free from dangerous and hazardous substances, and the place of work is not restricted to the actual work site but may also include any area that the employee uses in connection with and in furtherance of the employment.